The cost of community outreach HIV interventions: a case study in Thailand - Kyaw Min Soe; Katharina Hauck; Sukhum Jiamton; Sukhontha Kongsin (BMC, 2022)
Abstract Background There was an estimated 440,000 people living with HIV in Thailand in 2018. New cases are declining rapidly thanks to successful prevention programs and scaling up of anti-retroviral therapy (ART). Thailand aims to achieve its commitment to end the HIV epidemic by 2030 and implemented a cascade of HIV interventions through the Reach-Recruit-Test-Treat-Retain (RRTTR) program. Methods This study focused on community outreach HIV interventions implemented by Non-Governmental Organizations (NGOs) under the RRTTR program in 27 provinces. We calculated unit cost per person reached for HIV interventions targeted at key-affected populations (KAPs) including men who have sex with men/ transgender (MSM/TG), male sex workers (MSW), female sex workers (FSW), people who inject drugs (PWID) and migrants (MW). We studied program key outputs, costs, and unit costs in variations across different HIV interventions and geographic locations in Thailand. We used these estimates to determine costs of HIV interventions and evaluate economies of scale. Results The interventions for migrants in Samut Sakhon was the least costly with a unit cost of 21.6 USD per person to receive services, followed by interventions for migrants in Samut Prakan 23.2 USD per person reached, MSM/TG in Pratum Thani 26.5USD per person reached, MSM/TG in Nonthaburi 26.6 USD per person reached and, MSM/TG in Chon Buri with 26.7 USD per person. The interventions yielded higher efficiency in large metropolitan and surrounding provinces. Harm reduction programs were the costliest compare with other interventions. There was association between unit cost and scale of among interventions indicating the presence of economies scale. Implementing HIV and TB interventions jointly increased efficiency for both cases. Conclusion This study suggested that unit cost of community outreach HIV and TB interventions led by CSOs will decrease as they are scaled up. Further studies are suggested to follow up with these ongoing interventions for identifying potential contextual factors to improve efficiency of HIV prevention services in Thailand.